2020
DOI: 10.1021/acsami.0c00353
|View full text |Cite
|
Sign up to set email alerts
|

QCM-D Study of Time-Resolved Cell Adhesion and Detachment: Effect of Surface Free Energy on Eukaryotes and Prokaryotes

Abstract: Cell–material interactions are crucial for many biomedical applications, including medical implants, tissue engineering, and biosensors. For implants, while the adhesion of eukaryotic host cells is desirable, bacterial adhesion often leads to infections. Surface free energy (SFE) is an important parameter that controls short- and long-term eukaryotic and prokaryotic cell adhesion. Understanding its effect at a fundamental level is essential for designing materials that minimize bacterial adhesion. Most cell ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 68 publications
(138 reference statements)
1
46
0
Order By: Relevance
“…Surface energy is regarded as a measure of the unsaturated bond energy caused by the hanging bond of the surface material [46,47]. It can affect the activity of cells.…”
Section: Surface Energy Of Substratementioning
confidence: 99%
“…Surface energy is regarded as a measure of the unsaturated bond energy caused by the hanging bond of the surface material [46,47]. It can affect the activity of cells.…”
Section: Surface Energy Of Substratementioning
confidence: 99%
“…The results demonstrated that tuning the surface free energy of materials is a useful strategy for selectively promoting eukaryotic cell adhesion and preventing bacterial adhesion [18] Oxidative stress on the viscoelastic properties of pre-osteoblast cells…”
Section: Application Examples Technical Feature Technical Characteristicsmentioning
confidence: 98%
“…As a result, the adhered mass may not be determined accurately when only Δ f is measured. Therefore, quartz crystal microbalance with dissipation monitoring (QCM‐D) or resistance measurement will be more robust for biosensing of Salmonella because it can measure the changes in both frequency and energy dissipation (Δ D ) or motional resistance (Δ R ), corresponding to the changes in mass and viscoelastic properties of the adhered layer (Yongabi et al., 2020). Though Su and Li (2005a) reported a QCM biosensor for S .…”
Section: Biosensors With Different Transduces For Detection Of Salmonmentioning
confidence: 99%